Analytical and Numerical Study on Magnetoconvection Stagnation-Point Flow in a Porous Medium with Chemical Reaction, Radiation, and Slip Effects - Niranjan, H.; Sivasankaran, S.; Bhuvaneswari, M. (Hindawi Publishing Corporation, 2016)
We investigate the effects of slip and radiation on magnetoconvection flow of a chemically reacting fluid near a stagnation-point towards a vertical plate embedded in a porous medium analytically and numerically. The governing partial differential equations are diminished into the coupled ordinary differential equations by similarity transformations. Then they are solved analytically by homotopy analysis method and solved numerically by shooting method with RK fourth-order method. In this study, the analytical and numerical results are compared for many combinations of parameters. The rates of heat and mass transfer are calculated. The velocity profile near the plate overshoots on increasing the slip parameter. The concentration and temperature are decreasing on increasing the slip parameter.